Response preparation and intra-individual reaction time variability in schizophrenia - Dankinas, Denisas; Mėlynytė, Sigita; Šiurkutė, Aldona; Dapšys, Kastytis (Acta medica Lituanica, 2016)
Background. It is important to prepare response in advance to increase the efficiency of its execution. The process of response preparation is usually studied using the precueing paradigm. In this paradigm subjects have to employ the preceding information about further imperative stimulus to perform proper response preparation, which shortens the reaction time of subsequent response execution. Previous studies detected the impairment of response preparation in schizophrenia only with the help of electroencephalographic parameters, but not with the assessing of reaction time. Therefore, in this study we attempted to find a behavioural parameter that could detect impairment in response preparation of schizophrenia patients. It was recently found that appropriate response preparation not only shortens the reaction time but also increases its stability, which is measured with the intra-individual reaction time variability. It was also revealed that response stability could better find cognitive dysfunction in some studies of schizophrenia disorder than classical behavioural parameters. Hence, the main goal of this study was to verify if intra-individual reaction time variability could detect the impairment of response preparation in schizophrenia patients. Materials and methods. In order to achieve the main purpose, we carried out a study with 14 schizophrenia patients and 14 control group subjects. We used precueing paradigm in our research, in which participants had to employ information about stimulus probability for the  proper response preparation. Results. Our main result showed that despite the  responses of schizophrenia patients were faster to the  high-probability stimulus than to the low-probability one (F (1, 13) = 30.9, p
Keywords: response preparation; response stability; intra-individual reaction time variability; schizophrenia